3D printing creates patterned membranes. Issue 12 (December 2016) - Unknown
Abstract : Researchers in the USA at Pennsylvania State University have developed a new type of 3D printing which, they claim, will make it possible for the first time to rapidly prototype and test polymer membranes that are patterned for improved performance. This approach has the potential to enable rapid advances in membrane technology.